Assessing asphalt mixture moisture susceptibility through intrinsic adhesion, bitumen stripping and mechanical damage - Grenfell, James; Ahmad, Naveed; Liu, Yawen; Apeagyei, Alex K.; Large, David R.; Airey, Gordon (Taylor & Francis, 2014)
Durability is one of the most important properties of an asphalt mixture. A key factor affecting the durability of asphalt pavements is moisture damage. Moisture damage is generally considered to be the result of two main mechanisms; the loss of adhesion between bitumen and the aggregate and the loss of cohesion within the mixture. Conventional test methods for evaluating moisture damage include tests conducted on loose bitumen-coated aggregates and those conducted on compacted asphalt mixtures. This paper looks at results from the rolling bottle and the saturated ageing tensile stiffness (SATS) tests in an attempt to better understand the underlying processes and mechanisms of moisture damage with the help of surface energy measurements on the constituent bitumen and aggregates. Combinations of materials were assessed using both the rolling bottle and SATS tests. The surface energy properties of the binders were measured using a dynamic contact angle analyser and those of the aggregates using a dynamic vapour sorption device. From these surface energy measurements, it was possible to predict the relative performance of both the simple rolling bottle test and the more complicated SATS test. Mineralogical composition of the aggregates determined using a mineral liberation analyser was used to explain the differences in performance of the mixtures considered.